Running wheel training does not change neurogenesis levels or alter working memory tasks in adult rats - Acevedo-Triana,Cesar A.; Rojas,Manuel J.; Cardenas,Fernando P. (PeerJ, 2017)
Background Exercise can change cellular structure and connectivity (neurogenesis or synaptogenesis), causing alterations in both behavior and working memory. The aim of this study was to evaluate the effect of exercise on working memory and hippocampal neurogenesis in adult male Wistar rats using a T-maze test. Methods An experimental design with two groups was developed: the experimental group (n = 12) was subject to a forced exercise program for five days, whereas the control group (n = 9) stayed in the home cage. Six to eight weeks after training, the rats’ working memory was evaluated in a T-maze test and four choice days were analyzed, taking into account alternation as a working memory indicator. Hippocampal neurogenesis was evaluated by means of immunohistochemistry of BrdU positive cells. Results No differences between groups were found in the behavioral variables (alternation, preference index, time of response, time of trial or feeding), or in the levels of BrdU positive cells. Discussion Results suggest that although exercise may have effects on brain structure, a construct such as working memory may require more complex changes in networks or connections to demonstrate a change at behavioral level.
Keywords: Bromodeoxyuridine; Working memory; T maze; Wistar rats; Neurogenesis